Surgical anatomy of the anterior musculocapsular complex of the hip: a macroscopic and microscopic anatomical reappraisal - Benes, Michal; Bartak, Vladislav; Uhlik, Jiri; Novotny, Tomas; Rybakova, Aneta; Kachlik, David; Kunc, Vojtech (Anatomy & cell biology, 2025)
This study aimed to delineate the macroscopic and microscopic topography of muscles surrounding the anterior aspect of the hip joint and the underlaying joint capsule. Seven fresh-frozen cadavers were bilaterally dissected as per study protocol. Eleven hip joints were evaluated macroscopically, while three hip joints underwent histological analysis. Additionally, twenty hip bones and femurs were examined for the osseous morphology near the anterior portion of the articulating surfaces. Macroscopically, the rectus femoris muscle contributed to the articular capsule exclusively through its reflected head. The iliocapsularis and iliopsoas muscles were in direct contact with the articular capsule. Although the iliocapsularis muscle was adherent to the capsule throughout its whole course, the iliopsoas muscle was connected to the capsule through the iliopectineal bursa. Microscopically, different spatial thickness of the capsule was observed, with the thicker regions corresponding to the capsular ligaments. Osseous landmarks, relevant to the course of the iliopsoas muscle, included the iliopsoas notch and a groove for the psoas major muscle. Furthermore, split of the anterior inferior iliac spine and the "subspine" were constant findings corresponding to the origin of the direct head of the rectus femoris and the iliocapsularis muscles, and attachment of the medial band of the iliofemoral ligament, respectively. On the head of the femur, the Poirier's facet (35.0%), the Allen's fossa (60.0%), and the so-called plaque (50.0%) were observed. Conclusively, we introduce the concept of a four-layered anterior musculocapsular complex of the hip, aiming to aid the orthopaedic surgeon in both hip replacement and preservation procedures.
Keywords: Iliocapsularis muscle; Acetabulum; Iliopsoas muscle; Proximal femur; Hip capsule